Influence of Soil Plugging on Dynamic Soil Response During Simulated Pipe Pile Driving Model Test in Sands - Songchao Lin; Ye Lu; Chong Zhao (Applied Sciences)
The squeezing effect and strike-induced vibration generated by pile driving pose a threat to adjacent structures. To mitigate the squeezing effect, open-ended pipe piles were implemented. However, this type of pile brings a degree of soil-plugging effect, particularly in sandy soil, which complicates the squeezing effect and the dynamic responses of the pile during pile driving. In this study, model experiments were conducted using both open-ended piles and open-ended piles with different fixed-length soil plugs to investigate the squeezing effect and dynamic responses of the piles. Moreover, spectrum analysis was performed to explore the patterns of vibration waves in the open-ended pipe pile during the striking process. For open-ended pipe piles, acceleration fluctuations were detectable solely when the pile reached the sensor depth and at the end of the pile driving process, which revealed that the hammering energy was mainly consumed by pile settlement and the formation of the soil plug. When the formation of the soil plug was completed, the majority of the energy was converted into propagating vibration, resulting in the emergence of another crest of acceleration. The spectrum analysis revealed that the maximum amplitude occurred when the penetration depth was equal to half of the pile length.